THE EFFECTIVENESS OF THE PROCESS–PRODUCT APPROACH IN DEVELOPING UNIVERSITY STUDENTS’ CREATIVITY IN WRITING RECOUNT TEXTS - Benny Krisbiantoro (JR-ELT (Journal of Research in English Language Teaching), 2025)
This quasi-experimental study investigated the effectiveness of the process–product approach in enhancing the creativity of EFL university students in writing recount texts. The study involved 80 third-semester Islamic Broadcasting Communication (KPI) students selected through cluster sampling, with KPI-D (n = 40) assigned as the experimental group and KPI-E (n = 40) as the control group. Creativity and recount writing performance were measured through pre- and post-tests using an analytical rubric evaluating fluency, originality, elaboration, and organization. The experimental group showed substantial improvement, increasing from M = 63.75 (SD = 7.90) to M = 80.55 (SD = 6.80), while the control group improved from M = 64.50 (SD = 7.35) to M = 73.02 (SD = 6.88). Paired-samples t-tests revealed significant gains in both groups, with the improvement in the experimental group being markedly greater, t(39) = –14.88, p < .001, compared to the control group, t(39) = –7.45, p < .001. An independent-samples t-test further confirmed a significant difference in post-test scores between the groups, t(78) = 8.65, p < .001. Analysis of writing subcomponents revealed that students taught through the process–product approach outperformed their peers in content elaboration, grammar accuracy, vocabulary use, and coherence. These results demonstrate that the process–product approach is highly effective in fostering creativity and improving the overall quality of students’ recount writing.